Wild birds as potential reservoirs of antimicrobial-resistant Escherichia coli: a systematic review - Mbuthia, Catherine W.; Hoza, Abubakar S. (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) is currently a major global problem affecting humans, animals, and the environment. The role of wild birds in this epidemiological circuit has been the subject of several studies, but it is still far from being assessed. This review summarizes findings from 51 studies published between 2014 and 2024, examining resistant Escherichia coli (E. coli) from wild birds, with a focus on extended-spectrum beta-lactams (ESBLs) and other World Health Organization critically important antimicrobials for human medicine (WHO CIA List). The analysis reveals higher levels of AMR E. coli in wild birds in low and middle-income countries than in high-income countries (HICs). Particularly concerning is the high resistance observed to WHO CIA List: 100% resistance to cefotaxime, ceftazidime, nalidixic acid, gentamicin, and over 90% resistance to ciprofloxacin. Among the ESBL-producing E. coli, the genes coding for ESBLs (blaESBL) were predominant (76.5%, 377/493). Key gaps in the existing studies include: limited understanding of the sources of AMR for wild birds, limited comparative analyses of AMR in wild birds and other One Health sectors, and minimal longitudinal and satellite-tracking or telemetry approaches to monitor the persistence and transboundary movements of AMR in these birds. To address this, we advocate using standardized sampling methods, longitudinal studies incorporating satellite tracking, and whole-genome sequencing to better elucidate the role of wild birds in the global dissemination of AMR. Additionally, we emphasize the need to strengthen AMR surveillance in wild birds improve data reporting, and implement robust environmental management strategies within the One Health context to mitigate AMR transmission by wild birds.